A Preliminary Investigation into Worry about Mental Health: Development of the Mental Health Anxiety Inventory - Commons, D.; Greenwood, K.; Anderson, Rebecca (Cambridge University Press, 2015)
Background: Worry about physical health is broadly referred to as health anxiety and can range from mild concern to severe or persistent anxiety such as that found in DSM-IV hypochondriasis. While much is known about anxiety regarding physical health, little is known about anxiety regarding mental health. However, recent conceptualizations of health anxiety propose that individuals can experience severe and problematic worry about mental health in similar ways to how people experience extreme worry about physical health. Aims: Given the paucity of research in this area, the aim of the current study was to explore anxiety regarding mental health through validation of the Mental Health Anxiety Inventory (MHAI), a modified version of the Short Health Anxiety Inventory. Method: The MHAI, and measures of state anxiety (Depression, Anxiety and Stress Scales-21), trait worry (Penn State Worry Questionnaire), and health anxiety (Short Health Anxiety Inventory) were administered to 104 adult volunteers from the general community. Results: The MHAI demonstrated high internal consistency, acceptable test-retest reliability, and good construct validity when correlated with other measures of anxiety. Results also indicated that participants worried about their mental health and physical health equally, and that almost 9% of participants reported levels of mental health anxiety that were potentially problematic. Conclusion: Preliminary results suggest that a small proportion of adults in the community may experience high levels of mental health anxiety requiring treatment, and that the MHAI, if validated further, could be a useful tool for assessing this form of anxiety.